The Effectiveness of the Electronic Platform of the Central Bank of Iraq in Controlling the Parallel Exchange Rate: An Econometric Study for the Period 2021–2024 - Ayad Omar Sulaiman; Akram Salih Yousif; Mamon Adam Maarof (Diponegoro Journal of Economics, 2026)
Between 2021 and 2024, the Central Bank of Iraq (CBI) replaced its traditional foreign currency auction with a compliance-driven electronic platform aligned with SWIFT protocols, anti-money laundering (AML) directives, and counter-terrorism financing (CFT) requirements. This shift constituted a structural rupture in how Iraqi market participants accessed U.S. dollars. This paper examines the economic consequences of that rupture, focusing on the behaviour of the parallel exchange rate. Through theoretical, chronological, and econometric lenses, the study argues that the widening parallel market premium during 2023 was driven less by deteriorating macroeconomic fundamentals than by institutional friction embedded in the platform’s early operational design. The central finding is that every ten-percentage-point rise in the platform’s rejection rate corresponded to a three-to-five percent depreciation of the Iraqi dinar in informal markets, even as CBI reserves exceeded one hundred billion U.S. dollars. The paper documents partial stabilisation from late 2023 onward, driven by improved banking-sector compliance capacity and bilateral currency settlement arrangements, while acknowledging that a structurally rooted residual premium persists. This study is, to the authors’ knowledge, the first to model the platform’s operational performance—proxied by its monthly rejection rate—as a direct econometric determinant of the parallel exchange rate within an ARDL framework, introducing compliance friction as a measurable institutional variable. The paper contributes a novel institutional channel to the parallel exchange rate literature and offers evidence-based guidance for sequencing compliance reforms in state-dominated foreign exchange systems.